2010
DOI: 10.1002/ana.22024
|View full text |Cite
|
Sign up to set email alerts
|

Gentamicin‐induced readthrough of stop codons in duchenne muscular dystrophy

Abstract: The results support efforts to achieve drug-induced mutation suppression of stop codons. The immunogenic epitope resulting from readthrough emphasizes the importance of monitoring T-cell immunity during clinical studies that suppress stop codons. Similar principles apply to other molecular strategies, including exon skipping and gene therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
226
1
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 257 publications
(239 citation statements)
references
References 36 publications
3
226
1
5
Order By: Relevance
“…Consequently, aminoglycosides and ataluren have been explored as therapies for multiple genetic diseases caused by nonsense mutations, in which even a small amount of full-length functional protein may be sufficient to achieve a therapeutic effect. Clinical trials of these drugs have demonstrated some promise in Duchenne muscular dystrophy (DMD) and cystic fibrosis patients, although results have been inconsistent among trials (17)(18)(19).…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, aminoglycosides and ataluren have been explored as therapies for multiple genetic diseases caused by nonsense mutations, in which even a small amount of full-length functional protein may be sufficient to achieve a therapeutic effect. Clinical trials of these drugs have demonstrated some promise in Duchenne muscular dystrophy (DMD) and cystic fibrosis patients, although results have been inconsistent among trials (17)(18)(19).…”
Section: Significancementioning
confidence: 99%
“…Indeed, CD4 + Tcell (T CD4+ ) responses to a dystrophin epitope downstream of the PTC were detected in a recent clinical trial of gentamicin therapy for DMD (17). Furthermore, despite the lower frequency of readthrough at native stop codons, the high sensitivity of T cells may permit reactivity to cryptic epitopes encoded downstream of conventional stop codons as well.…”
Section: Significancementioning
confidence: 99%
“…8 Gentamycin and ataluren (PTC24), allowing nonsense mutation reversion, have completed phase II clinical trials. 9,10 The antisense oligonucleotides, such as AVI-4658 and PRO051, which induce exon 51 skipping, have completed phase II clinical trials; PRO051 is currently undergoing a phase III clinical trial. 11,12 Because all of these molecules target specific mutation types, the detailed location of a breakpoint is important in selecting appropriate participants for exon-skipping treatment.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10][11][12] Exon skipping, which rectifies the aberrant reading frame, aims to treat patients with large deletions; yet, to achieve this, the selection of appropriate patients with detailed genetic diagnosis is very important.…”
Section: Introductionmentioning
confidence: 99%
“…Pour le gène de la dystrophine, les résultats des tests cliniques sont également nuancés. La protéine dystrophine entière a été détectée chez certains patients et atteignait jusqu'à 15 % du niveau de la protéine sauvage mais sans permettre un bénéfice thérapeutique clair [15][16][17]45]. Le succès de cette approche dépend du taux de réexpression de la protéine complète qui est nécessaire pour permettre un bénéfice thérapeutique.…”
Section: Pertinence De L'approche Thérapeutique En Fonction Des Difféunclassified